Ethno-Nationalistic Dimensions of Afghan Conflict and Prospects of Reconciliation after American Exit - Muhammad Ajmal Abbasi, (ASIAN Journal of International Peace & Security (AJIPS), 2022)
Afghanistan came into being after the fragmentation of Persian and Moghul Empires, essentially a process of fission - a proclivity that has since been deeply imbedded in the Afghan socio-political culture. Historically, Afghan national dynamics have been marred with the internal disharmony and external military invasions that not only promoted instability but also seriously impeded evolution of national integrity in the country. After the exit of the coalition forces and return of the Taliban at Kabul, Afghanistan continues to find itself entrapped in ethno-nationalistic conflict, making a broad-based and sustainable reconciliation vital for the survival of the country. However, the challenge of reconciling Afghan society seems even arduous when decades of internal conflict, discord and trust deficit on the basis of ethno-nationalistic divergences is taken into account. This paper aims at dilating upon the historical antecedents of Afghan internal conflict emanating from ethnic dissentions and evaluates the prospects of reconciliation after American exit.